The art and science of analyzing software data - Bird, John; Menzies, Tim; Zimmermann, Thomas (Amsterdam Elsevier, 2020)
A comprehensive guide to the art and science of analyzing software data, with best practices generated by leading data scientists, collected from their experience training software engineering students and practitioners on how to master data science.
Keywords: Data mining; Computer software -- Data processing; Electronic data processing; Softwareentwicklung; Data Mining; Datenanalyse